2019
DOI: 10.1080/21645698.2019.1625653
|View full text |Cite
|
Sign up to set email alerts
|

Development of a rapid and highly efficient Agrobacterium -mediated transformation system for pigeon pea [ Cajanus cajan (L.) Millsp]

Abstract: An efficient genetic transformation system is a prerequisite for studying gene functions, molecular breeding program, and introducing new traits. Agrobacterium tumefaciens-mediated genetic transformation is a widely preferred and accepted method for many plants, including pigeon pea. However, the efficiency of transformation of pigeon pea using the existing protocols is low and time-consuming. In the present study, we developed a rapid and highly efficient transformation system of pigeon pea, using embryonic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…F. hindsii is a model species for citrus studies and has complete genome sequencing and assembly [ 18 ]. However, due to the limitation of genotype dependence, the transformation efficiency of F. hindsii is much lower than that of other crops, which increases the workload and further hinders research on citrus genetics and functional genomics [ 35 , 36 ]. In this study, we confirmed that the CRISPR/Cas9 system with pK7WG2D as the binary vector can efficiently edit the genome of F. hindsii , while the pMDC32 vector was not suitable for F. hindsii ( Figs 2 and 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…F. hindsii is a model species for citrus studies and has complete genome sequencing and assembly [ 18 ]. However, due to the limitation of genotype dependence, the transformation efficiency of F. hindsii is much lower than that of other crops, which increases the workload and further hinders research on citrus genetics and functional genomics [ 35 , 36 ]. In this study, we confirmed that the CRISPR/Cas9 system with pK7WG2D as the binary vector can efficiently edit the genome of F. hindsii , while the pMDC32 vector was not suitable for F. hindsii ( Figs 2 and 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Karmakar et al reported the use of a non-tissue culture-based method to obtain the transformation efficiency of 83% from embryonic axis-attached cotyledons [60]. Low transformation frequencies from 13.7 % to 32% have been shown in T1 generation using embryogenic calli obtained from different explants via agrobacterium-mediated transformation [61,62,63].…”
Section: Discussionmentioning
confidence: 99%
“…It was used as a selection marker for the production of recombinant proteins in the pea transient expression by agroinfection (Fan et al 2011). Its successful usage for Arobacterium-mediated transformation of pigeon peas has been described by Karmakar et al (2019). A summary of the selection and reporter genes used for the pea transformation in different studies is presented in Table 2.…”
Section: Selective and Reporter Genes Used For Pea Transformationmentioning
confidence: 99%